The Effect of Ownership Structure on Tax Aggressiveness - Shinta Kameliya; Ani Wilujeng Suryani (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2026)
This study aims to analyze the effect of ownership structure on corporate taxaggressiveness, using the Cash Flow Effective Tax Rate (CFETR) as the main measure.Ownership structure is measured based on the proportion of institutional andmanagerial ownership in a company. This study involved 61 samples of companies inthe energy sector listed on the Indonesia Stock Exchange (IDX) from 2018 to 2023. Dataobtained from company annual reports were processed using the Generalized LeastSquare (GLS) technique, while considering control factors such as profitability, auditortype, company age, and company size. The main findings reveal that institutionalownership affects CFETR in the opposite direction. Given that CFETR has an inverserelationship with tax aggressiveness, these findings indicate that an increase ininstitutional ownership is associated with an increase in corporate tax aggressiveness.On the other hand, managerial ownership was not found to have an effect on CFETR.These results underscore that in the context of Indonesian energy companies,institutional investors do not yet fully function as a supervisory mechanism capable ofcurbing aggressive tax planning practices, while management share ownership is notyet strong enough to influence corporate tax policy.